THE CURRENT STATE OF DIGITALIZATION IN HIGHER EDUCATION (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes the current state of the digitalization process in primary education, the existing technologies, their impact on the educational process, and their applicability. It also highlights the advantages and challenges of digital tools in primary school lessons. The paper examines pressing issues in the field and possible solutions.